Genetic inactivation of PERK signaling in mouse oligodendrocytes: Normal developmental myelination with increased susceptibility to inflammatory demyelination. Issue 5 (31st January 2014) - Hussien, Yassir; Cavener, Douglas R.; Popko, Brian
<x xml:space="preserve">Abstract</x> The immune‐mediated central nervous system (CNS) demyelinating disorder multiple sclerosis (MS) is the most common neurological disease in young adults. One important goal of MS research is to identify strategies that will preserve oligodendrocytes (OLs) in MS lesions. During active myelination and remyelination, OLs synthesize large quantities of membrane proteins in the endoplasmic reticulum (ER), which may result in ER stress. During ER stress, pancreatic ER kinase (PERK) phosphorylates eukaryotic translation initiation factor 2α (elF2α), which activates the integrated stress response (ISR), resulting in a stress‐resistant state. Previous studies have shown that PERK activity is increased in OLs within the demyelinating lesions of experimental autoimmune encephalomyelitis (EAE), a model of MS. Moreover, our laboratory has shown that PERK protects OLs from the adverse effects of interferon‐γ, a key mediator of the CNS inflammatory response. Here, we have examined the role of PERK signaling in OLs during development and in response to EAE. We generated OL‐specific PERK knockout (OL‐PERKko/ko) mice that exhibited a lower level of phosphorylated elF2α in the CNS, indicating that the ISR is impaired in the OLs of these mice. Unexpectedly, OL‐PERKko/ko mice develop normally and show no myelination defects. Nevertheless, EAE is exacerbated in these mice, which is correlated with increased OL loss, demyelination, and axonal degeneration. These data indicate that although not needed for developmental myelination, PERK signaling provides protection to OLs against inflammatory demyelination and suggest that the ISR in OLs could be a valuable target for future MS therapeutics. GLIA GLIA 2014;62:680–691